A multi‐aperture coupling liquid attenuator. Issue 14 (21st October 2021) - Yan, Dandan; Xing, Lei; Xu, Qian; Zhang, Guoxuan; Zhu, Jiajia
Abstract: A liquid attenuator with multi‐aperture coupling is proposed. It consists of two coupled rectangular waveguide cavities, two transparent containers and pure water. By utilising the multi‐aperture coupling structure, the proposed design achieves large attenuation with good flatness across a wide frequency range. The pure water is employed as the liquid loading to dissipate the energy. Both simulations and measurements have been conducted. It is demonstrated that the proposed attenuator exhibits an attenuation of 59.2 dB with an attenuation flatness of ±0.9 dB from 2.19 to 3.64 GHz (the reflection coefficient is less than −10 dB across the band). Compared with conventional waveguide attenuators, this design provides a wider frequency working range, a more compact size, larger and flatter attenuation and better heat dissipation. It can be a promising candidate for high power applications.